Two‐piece zirconia implants supporting all‐ceramic crowns: A prospective clinical study. Issue 4 (26th March 2014) - Cionca, Norbert; Müller, Nada; Mombelli, Andrea
Abstract: Objectives: The aim of this prospective clinical study is to evaluate the safety and efficacy of a new all‐ceramic implant system to replace missing teeth in partially edentulous patients. Material and methods: Thirty‐two partially edentulous, systemically healthy patients were treated with 49 two‐piece zirconia implants (ZERAMEX ® T Implant System). Zirconia abutments were connected with adhesive resin cement. Single‐unit full‐ceramic crowns were cemented. The cases have been followed for 588±174 days after loading (range 369–889 days). All patients have been re‐evaluated 1 year after loading. Results: The cumulative survival rate 1 year after loading was 87% implants. All failures were the result of aseptic loosening, and no implants were lost after the first year. The results of the other cases were good, and the patients were very satisfied. The cumulative soft tissue complication rate was 0%, the cumulative technical complication rate was 4% implants, the cumulative complication rate for bone loss >2 mm was 0%, and the cumulative esthetic complication rate was 0%. Including the data from 20 patients treated with an earlier version of the system, an over‐all 2‐year cumulative survival rate of 86% was calculated for a total of 76 two‐piece zirconia implants supporting all‐ceramic crowns in 52 patients. Conclusions: Replacement of single teeth in the posterior area was possible with this new full‐ceramic implant system. Failures were due to aseptic loosening.